Improving visual observation skills through the arts to aid radiographic interpretation in veterinary practice: A pilot study. Issue 5 (5th June 2017) - Beck, Cathy; Gaunt, Heather; Chiavaroli, Neville
Abstract: Radiographic interpretation is a perceptual and cognitive skill. Recently core veterinary radiology textbooks have focused on the cognitive (i.e., the clinical aspects of radiographic interpretation) rather than the features of visual observation that improve identification of abnormalities. As a result, the skill of visual observation is underemphasized and thus often underdeveloped by trainees. The study of the arts in medical education has been used to train and improve visual observation and empathy. The use of the arts to improve visual observation skills in Veterinary Science has not been previously described. Objectives of this pilot study were to adapt the existing Visual Arts in Health Education Program for medical and dental students at the University of Melbourne, Australia to third year Doctor of Veterinary Medicine students and evaluate their perceptions regarding the program's effects on visual observation skills and confidence with respect to radiographic interpretation. This adaptation took the form of a single seminar given to third year Doctor of Veterinary Medicine students. Following the seminar, students reported an improved approach to radiographic interpretation and felt they had gained skills which would assist them throughout their career. In the year following the seminar, written reports of the students who attended the seminar were compared with reports from a matched cohort of students who did not attend the seminar. This demonstrated increased identification of abnormalities and greater description of the abnormalities identified. Findings indicated that explicit training in visual observation may be a valuable adjunct to the radiology training of Doctor of Veterinary Medicine students.